دور الشيخ يوسف القرضاوي في تقرير مفهوم الوسطية ومعالمها: دراسة تحليلية من خلال مؤلفاته: The Role of Shaikh Yūsuf Al-Qaradāwi in Establishing the Concept of Al-Wasatiyyah and Its Features: An Analytical Study Through His Writings - شيخ الأعظم أبرار (الدراسات الإسلامية, 2025)
This study examines the contributions of Shaikh Dr. Yūsuf Al-Qaradāwi, one of the most influential Islamic scholars of the 21st century, in promoting and articulating the concept of Al-Wasatiyyah wal-I’tidāl (moderation and balance) in Islam. Recognized as a leading authority on this principle, Shaikh Al-Qaradāwi dedicated his life to clarifying its proper understanding through his writings, speeches, lectures, and academic supervision. This research explores how he defined and explained the features of Al-Wasatiyyah wal-I’tidāl in the light of the Qur’an and Sunnah, emphasizing its central role as a defining characteristic of Islam. The study employs an analytical approach to examine Shaikh Al-Qaradāwi’s works, highlighting his influence in guiding the Muslim Ummah toward a balanced understanding of Islamic teachings.